High-toughness self-repairing cation selective hydrogel film as well as preparation method and application thereof
By preparing a high-strength, tough, self-healing cation-selective hydrogel membrane, the problems of low selectivity and poor stability of traditional ion transport membranes were solved, achieving efficient permeation energy conversion and mechanical stability, and simplifying the preparation process.
Patent Information
- Application Number
- CN202511351409.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-22
- Publication Date
- 2026-01-02
AI Technical Summary
Traditional ion transport membranes have low ion selectivity, low permeation energy conversion efficiency, low mechanical stability, high manufacturing cost, and complex processes, which limits the widespread application of permeation energy.
A three-dimensional network was formed by cross-linking and polymerization of carboxylic acid-containing monomers, sulfonic acid-containing monomers, and polymers in the presence of a cross-linking agent. Combined with an ion transport medium, a high-strength, tough, self-healing, cation-selective hydrogel membrane was prepared. The large-scale preparation of the material was achieved through a photo-induced self-assembly strategy.
It improves cation selectivity and transport efficiency, enhances mechanical stability and self-healing properties, simplifies the preparation process, and is suitable for high-performance permeation energy conversion.
Smart Images

Figure CN121249082A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogel-based ion-selective membrane technology, and specifically discloses a high-strength, tough, self-healing cation-selective hydrogel membrane, its preparation method, and its application. Background Technology
[0002] Nanofluidics studies fluid and ion transport in nanoscale confined regions and has received widespread attention and wide application in multiple fields over the past two decades. Asymmetric ion channels in biological organisms can efficiently modulate transmembrane ion currents, laying the foundation for biomimetic nanofluidics research.
[0003] Numerous methods for fabricating synthetic artificial nanochannels have been proposed. For instance, ion beam and electron beam engraving can form nanopores in atomically thin materials, with thicknesses comparable to lipid bilayers; ion trajectory etching can create nanochannels with different geometries, similar to various shapes of biological ion channels. Intelligent nanofluidic channels can also be constructed by combining nature-inspired structures with constrained chemistry. For example, modifying conical gold nanotubes with thiol-terminated single-stranded DNA molecules can create synthetic intelligent nanochannels with voltage-dependent ion-gated behavior. Furthermore, ion rectification, gating, responsive conduction, and pumping have also been reproduced in synthetic channels.
[0004] Excitingly, ion-transport membrane nanofluidic channels with customized ion transport kinetics can harvest renewable osmotic energy—the release of Gibbs free energy resulting from the mixing of ion solutions of varying concentrations—between seawater and river water. This energy can be harvested and converted into electricity. It is estimated that the total amount of usable osmotic energy worldwide is approximately 1 TW. Compared to other energy sources such as wind and solar power, osmotic energy also has the advantage of minimal diurnal variation. Reverse electrodialysis based on ion-transport membranes, first proposed in 1954, is a key technology for capturing this blue energy. However, traditional ion-transport membranes exhibit low ion selectivity, resulting in low osmotic energy conversion efficiency and a power density of less than 2.2 W / m³. 2 However, the membranes also have drawbacks such as low mechanical stability, high preparation cost, and complex preparation process, which have become the main bottlenecks restricting the widespread application of permeation energy. Summary of the Invention
[0005] To address the aforementioned problems in existing technologies, this invention provides a high-strength, tough, self-healing cation-selective hydrogel membrane, its preparation method, and its applications. This hydrogel membrane exhibits superior cation selectivity, high strength and toughness, and self-healing properties, and is easy to prepare, making it suitable for high-performance permeation energy conversion.
[0006] In a first aspect, the present invention provides a high-strength, tough, self-healing, cationic selective hydrogel membrane, wherein the hydrogel membrane contains: i) a three-dimensional network formed by cross-linking polymerization of carboxylic acid monomers and sulfonic acid monomers in the presence of a cross-linking agent; ii) polymer chains selected from any one or a combination of two or more of poly(sodium 4-styrenesulfonate), poly(2-acrylamide-2-methyl-1-propanesulfonic acid), polyvinyl alcohol, or polyethylene glycol; and iii) an ion transport medium comprising ethyl 1-ethyl-3-methylimidazolium sulfate and water; the three-dimensional network and the polymer chains interpenetrate and intertwine to form an interpenetrating network structure; and the interpenetrating network structure is filled with an ion transport medium.
[0007] The hydrogel membrane contains carboxylic acid monomers, sulfonic acid monomers, crosslinking agents, and polymer chains, all carrying abundant negative charges. The interpenetrating network formed by these chains through chemical and physical interactions provides the framework and channels for ion transport, resulting in high strength and toughness. The ionic liquid and deionized water filling the membrane provide the medium for rapid ion transport. Therefore, this hydrogel membrane possesses abundant negative surface charges, a dense 3D pore structure, and a rapid ion transport medium, significantly improving cation transport efficiency.
[0008] In some embodiments, the carboxylic acid-containing monomer is selected from any one or more combinations of acrylic acid, acrylates, alkyl acrylic acid, alkyl acrylates or alkyl alkyl acrylates, preferably any one or more combinations of acrylic acid, methacrylic acid, sodium methacrylate, magnesium methacrylate, calcium methacrylate, lithium methacrylate, potassium acrylate, ethyl methacrylate, methyl methacrylate or hydroxyethyl methacrylate, more preferably acrylic acid.
[0009] In some embodiments, the sulfonic acid-containing monomer is selected from any one or a combination of two or more of alkylenylbenzenesulfonate, sulfonyl acrylate, alkylenamidoalkylpropanesulfonic acid, or alkylenamidoalkylpropanesulfonic acid, preferably any one or a combination of two or more of sodium 4-vinylbenzenesulfonate, lithium 4-vinylbenzenesulfonate, potassium 3-sulfopropyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid, or sodium 2-acrylamido-2-methylpropanesulfonic acid, more preferably 2-acrylamido-2-methylpropanesulfonic acid.
[0010] In some embodiments, the crosslinking agent is selected from acrylamide, acrylate, or phosphate crosslinking agents, preferably. N,N'- any one or a combination of two or more of the following: methylene bisacrylamide, tripropylene glycol diacrylate, bis(2-(methacryloyloxy)ethyl) phosphate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, 1,3,5-triacryloyl hexahydro-1,3,5-triazine or pentaerythritol tetraacrylate, more preferably bis(2-(methacryloyloxy)ethyl) phosphate.
[0011] In a second aspect, the present invention provides a composition for preparing the aforementioned hydrogel membrane, comprising: 1-3 parts by weight of a carboxylic acid monomer, 3-5 parts by weight of a sulfonic acid monomer, 0.1-0.3 parts by weight of a polymer, 0.4-0.6 parts by weight of a crosslinking agent, 3-5 parts by weight of 1-ethyl-3-methylimidazolium sulfate, 3-5 parts by weight of deionized water, and an appropriate amount of initiator.
[0012] In some embodiments, the initiator is selected from 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone or 2,2-azobisisobutylamidine dihydrochloride.
[0013] In some implementations, the amount of initiator is 0.04 to 0.06% of the total molar amount of the carboxylic acid monomer, the sulfonic acid monomer, and the crosslinking agent.
[0014] Thirdly, the present invention provides a method for preparing the aforementioned hydrogel membrane, which uses the aforementioned composition and includes: preparing a solution containing a carboxylic acid monomer, a sulfonic acid monomer, a polymer, a crosslinking agent, ethyl 1-ethyl-3-methylimidazolium sulfate, deionized water and an initiator under light-protected conditions, degassing to obtain a precursor solution; and subjecting the precursor solution to ultraviolet light irradiation for a certain period of time under oxygen-isolated conditions to photo-induced curing to obtain a hydrogel membrane.
[0015] In some embodiments, the carboxylic acid-containing monomers and sulfonic acid-containing monomers are first dissolved in deionized water and ethyl 1-ethyl-3-methylimidazolium sulfate, mixed thoroughly, and allowed to stand for 5-7 hours. Then, a crosslinking agent and a polymer are added, mixed thoroughly, and allowed to stand for 5-7 hours. Finally, a photoinitiator is added, and the mixture is mixed thoroughly under light-protected conditions. This process effectively prevents the assembly of components and prevents prepolymerization due to the strong interactions between components during mixing, which could lead to exothermic reactions and affect the hydrogel film performance. Light-protected treatment of the precursor solution, followed by nitrogen deoxygenation and centrifugal degassing, effectively prevents prepolymerization and defects in the hydrogel film.
[0016] In some implementation schemes, both carboxylic acid monomers and sulfonic acid monomers need to be purified by column chromatography before use, and solvents are removed by rotary evaporation and vacuum oven drying.
[0017] In some implementations, the polymer needs to have the polymerization inhibitor removed before use.
[0018] In some implementations, the centrifuge degassing is performed at a speed of 10,000 to 14,000 rpm, which can remove the gas from the precursor solution and thus prepare a uniform hydrogel membrane.
[0019] In some implementations, photo-induced curing is performed in a glove box at room temperature, which ensures that the photoinitiator can play its full role, thereby achieving a uniform 3D network structure and stable mechanical properties.
[0020] In some implementations, the power of ultraviolet light irradiation is 100~200W, the wavelength of ultraviolet light irradiation is 300~400nm, and the irradiation time is 20~40min.
[0021] In some embodiments, the reaction vessel includes a polytetrafluoroethylene (PTFE) reservoir and a tempered glass sealing cover on top of the reservoir. The reservoir also has an injection port and a vent. During operation, a syringe is used to draw the precursor solution and inject it into the injection port until liquid overflows from the vent, thereby effectively preventing foaming during the injection of the precursor solution and ensuring that the prepared hydrogel membrane has stable structure and mechanical properties.
[0022] In some implementation schemes, the reaction vessel is cleaned with deionized water and ethanol before use, then dried and cooled before use.
[0023] Fourthly, this invention provides the application of the aforementioned hydrogel membrane in reverse electrodialysis salinity gradient power generation. The hydrogel membrane prepared by this invention is a cation-selective membrane capable of selectively transporting cations, and can be applied to the conversion of osmotic energy. Furthermore, the performance of the hydrogel membrane can be further controlled by optimizing the raw materials used in its preparation, achieving controllability of thickness and surface charge content. For example, by controlling the thickness, a longer three-dimensional transport channel can be obtained, and other target performance can be further achieved for applications in energy storage, intelligent detection, and other fields.
[0024] The beneficial effects of this invention are as follows: 1. The hydrogel membrane provided by this invention contains carboxylic acid monomers, sulfonic acid monomers, and a large number of negative charges carried in the polymer chains, resulting in an overall negative charge and thus exhibiting excellent cation selectivity. The three-dimensional network polymer framework provides an excellent carrier for ion transport channels. The interpenetrating network structure formed by the interpenetration and entanglement of the polymer chains significantly improves the mechanical stability of the hydrogel membrane, giving it high strength and toughness. Furthermore, the electrostatic interactions between structural units within the three-dimensional network polymer framework and between the structural units and the polymer chains further enhance the mechanical stability of the hydrogel membrane, while also giving it excellent self-healing properties. The ion transport medium filled in the interpenetrating network improves the rapid cation transport capability of the hydrogel membrane. Therefore, the hydrogel membrane of this invention possesses superior cation selectivity, rapid ion transport capability, ultra-toughness, and self-healing properties.
[0025] 2. The composition provided by this invention, on the one hand, has monomers, crosslinking agents, and polymer chains carrying a large number of negatively charged groups, resulting in a hydrogel membrane with a higher surface charge density than traditional hydrogel membranes, thus exhibiting better cation selectivity. On the other hand, by optimizing the ratio of monomers, crosslinking agents, ion transport media, and polymers, it is beneficial to prepare hydrogel membranes with a uniform 3D network structure, uniform surface charge, and uniform 3D nanochannel structure, providing abundant channels for ion transport. This uniform membrane structure with a large number of negative charges has excellent application prospects in the field of nanofluidics.
[0026] 3. This invention employs a photoinduced self-assembly strategy to prepare hydrogel membranes. The preparation method is simple and can achieve large-scale material preparation. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the preparation method of HIC membrane; Figure 2 These are SEM images of different membranes: A: HIC membrane; B: HIC-N membrane; C: HIC-S membrane; Figure 3 These are FTIR images of the HIC membrane and AA and AMPS; Figure 4 Stress-strain curves of different membranes: A: HIC membrane; B: HIC-N membrane; C: HIC-S membrane; Figure 5 This is a Zeta potential diagram of the HIC membrane, HIC-N membrane, and HIC-S membrane; Figure 6 This is a diagram of a conductivity cell device used for testing the ion transport performance of HIC membranes. Figure 7These are the ion transport performance test results of different membranes in KCl solution; A: I-V curves of HIC membrane measured in KCl solution of different concentrations; B: Conductivity of HIC membrane measured in KCl solution of different concentrations; C: I-V curves of HIC-S membrane measured in KCl solution of different concentrations; D: Conductivity of HIC-S membrane measured in KCl solution of different concentrations. Figure 8 These are the ion transport performance test results of different membranes; A: IV curves of HIC membranes tested at different positive and negative electrode positions; B: Comparison of power density test results before and after HIC membrane fracture healing; C: Comparison of IV curves of HIC membrane, HIC-N membrane and HIC-S membrane; D: Comparison of power density test results of HIC membrane, HIC-N membrane and HIC-S membrane after fracture healing. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] In the following examples, AMPS: 2-acrylamido-2-methylpropanesulfonic acid; AA: acrylic acid; NS: 1-ethyl-3-methylimidazolium sulfate; BMEP: bis(2-(methacryloyloxy)ethyl) phosphate; PSS: sodium poly(4-styrenesulfonate).
[0030] Example 1: High-strength, tough, self-healing, cationic selective hydrogel membrane (HIC), prepared as follows: Step 1: Preparation of HIC precursor solution. Dissolve 5g of AMPS and 1g of AA in 4g of deionized water and 4g of normal saline, then sonicate until clear. After stabilization for 6 hours, add 0.5g of BMEP, followed by 0.2g of PSS, mix thoroughly for 10 minutes, let stand for 6 hours, then add 0.05mol% of photoinitiator I2959 (based on the total molar amount of monomers AMPS and AA and crosslinking agent BMEP). Stir thoroughly for 15 minutes under light-protected conditions, then bubble with nitrogen to remove oxygen, and finally centrifuge at 12000 rpm to remove bubbles and obtain the precursor solution.
[0031] Preparation of HIC-N precursor solution: 5 g of AMPS and 1 g of AA were dissolved in 8 g of deionized water, and then sonicated until clear. After stabilization for 6 h, 0.5 g of BMEP was added, followed by 0.2 g of PSS. The mixture was homogenized for 10 min, allowed to stand for 6 h, and then 0.05 mol% of photoinitiator I2959 (based on the total molar amount of monomers AMPS and AA and crosslinking agent BMEP) was added. The mixture was stirred for 15 min under light-protected conditions, then oxygen was removed by bubbling with nitrogen, and finally centrifuged at 12000 rpm to obtain the precursor solution.
[0032] Preparation of HIC-S precursor solution: 6 g of AA was dissolved in 4 g of deionized water and 4 g of normal saline, and then sonicated until clear. After stabilization for 6 h, 0.5 g of BMEP was added, followed by 0.2 g of PSS. The mixture was homogenized for 10 min, allowed to stand for 6 h, and then 0.05 mol% of photoinitiator I2959 (based on the total molar amount of monomers AMPS and AA and crosslinking agent BMEP) was added. The mixture was stirred for 15 min under light-protected conditions, then oxygen was removed by bubbling with nitrogen, and finally centrifuged at 12000 rpm to remove bubbles and obtain the precursor solution.
[0033] Step 2: Clean the polytetrafluoroethylene reaction vessel (with injection hole and gas vent) and tempered glass sealing cover with deionized water and ethanol, then dry it in a 60°C oven for 2 hours and let it cool before use.
[0034] Step 3: Transfer the above precursor solution, PTFE reaction vessel, tempered glass cover, 10mL syringe, and UV lamp (365nm) to the glove box. After assembling the tempered glass cover and PTFE mold, use the syringe to draw the precursor solution and inject it into the injection hole until liquid overflows from the vent hole. After irradiating with the UV lamp for 30 minutes, a high-strength, tough, self-healing, cation-selective hydrogel membrane is obtained, denoted as HIC membrane. The preparation process is as follows: Figure 1 As shown.
[0035] Comparative Example 1 The difference from Example 1 lies in step 1, specifically: preparation of the HIC-N precursor solution. 5g of AMPS and 1g of AA were dissolved in 8g of deionized water, and then sonicated until clear. After stabilization for 6 hours, 0.5g of BMEP was added, followed by 0.2g of PSS. The mixture was homogenized for 10 minutes, allowed to stand for 6 hours, and then 0.05 mol% of photoinitiator I2959 (based on the total molar amount of monomers AMPS and AA, and crosslinking agent BMEP) was added. The mixture was stirred for 15 minutes under light-protected conditions, then oxygen was removed by bubbling with nitrogen, and finally, the precursor solution was obtained by centrifugation at 12000 rpm. The final membrane is designated as the HIC-N membrane.
[0036] Comparative Example 2 The difference from Example 1 lies in step 1, specifically: preparation of the HIC-S precursor solution. 6g of AA was dissolved in 4g of deionized water and 4g of normal saline, and then sonicated until clear. After stabilization for 6 hours, 0.5g of BMEP was added, followed by 0.2g of PSS. The mixture was homogenized for 10 minutes and allowed to stand for 6 hours. Then, 0.05 mol% of photoinitiator I2959 (based on the total molar amount of monomers AMPS and AA, and crosslinking agent BMEP) was added. The mixture was stirred for 15 minutes under light-protected conditions, then oxygen was removed by bubbling with nitrogen. Finally, the mixture was centrifuged at 12000 rpm to remove bubbles and obtain the precursor solution. The resulting membrane is designated as the HIC-S membrane.
[0037] I. Structural Characterization like Figure 1 As shown, the final prepared HIC membrane contains a three-dimensional network formed by cross-linking of blue monomers (AMPS and AA), which interpenetrates and entangles with magenta polymer chains (PSS) to form an interpenetrating network structure. This interpenetrating network structure is filled with pink ion transport media (NS and water).
[0038] like Figure 2 As shown, HIC membrane (A) and HIC-S membrane (C) have a uniform and dense 3D network structure, exhibiting stable mechanical properties and providing abundant nanochannels for ion transport. HIC-N membrane (B) has a porous structure with weak interactions between its components, resulting in weak mechanical properties and a lack of self-healing ability.
[0039] like Figure 3 As shown, the decrease in the C=C characteristic absorption peak of the monomer AMPS indicates that the HIC membrane was successfully prepared by curing.
[0040] like Figure 4As shown, the stress-strain curve of a normal HIC membrane exhibits a fracture stress exceeding 6 MPa and an elongation at break exceeding 550%, indicating that the prepared HIC membrane possesses superior toughness. Even after 30 seconds of fracture healing, it still maintains a fracture stress exceeding 3 MPa and an elongation at break exceeding 400% (A). The strain of the HIC-S membrane reaches as high as 8.6 MPa (C), while the fracture stress of the HIC-N membrane is only 0.7 MPa (B).
[0041] like Figure 5 As shown, the HIC membrane exhibits a lower zeta potential than the monomers AMPS and AA, indicating a synergistic effect among the monomers after curing, resulting in stronger cation selectivity. The HIC membrane has the lowest zeta potential, followed by the HIC-N and HIC-S membranes, with the cation selectivity ranking as HIC membrane > HIC-N membrane > HIC-S membrane. The HIC membrane has more sulfonic acid groups than the HIC-S membrane, hence its lower zeta potential and higher cation selectivity. Because the HIC-N membrane lacks NS, NS not only maintains the overall mechanical stability of the membrane during ion transport but also exhibits cation selectivity due to its positive and negative charges. The synergistic effect between the negative charge provided by NS and the hydrogel network further contributes to the lower zeta potential of the HIC membrane compared to the HIC-N membrane.
[0042] II. Ion transport performance test Ion transport performance testing was performed using two commonly used acrylic semi-conducting cells, with the HIC membrane sandwiched between the two cells. Ions containing 3×10⁻⁶ molecules were placed on both sides of the membrane. -8 m 2 The small window on the silicon wafer is used to determine the current density. For example... Figure 6 As shown, during the test, two silver silver chloride electrodes were used to connect the entire circuit, and a picoammeter was used to monitor the current.
[0043] like Figure 7 As shown, the HIC membrane exhibits linear ohmic behavior in the IV response of KCl solutions at all concentrations (A), indicating that the HIC membrane has a uniform microstructure. The slopes of these linear IV curves were then calculated to obtain the conductivity of the HIC membrane at different KCl solution concentrations. When the KCl solution concentration is less than 0.1 M, the conductivity begins to deviate from the matrix value, indicating that ion transport in the HIC membrane is controlled by surface charge (B). Due to the low surface charge of the HIC-S membrane, its ability to control cations is weak, and the internal electrostatic interactions are too strong, resulting in very low conductivity (C, D).
[0044] like Figure 8 As shown, the ion selectivity test selected 10. -1 M and 10 -4M KCl solution. The ion selectivity was determined by changing the positions of the positive and negative electrodes. When the positive electrode was at a high concentration, the concentration gradient direction was aligned with the electric field direction, thus favoring cation transport. Considering the superior cation selectivity of the HIC membrane, the IV curve shifted upwards. When the negative electrode was on the high concentration side, the concentration gradient direction was opposite to the electric field direction, favoring anion transport, which contradicted the superior cation selectivity of the HIC membrane, so the IV curve shifted downwards. When the positive electrode was connected to the high concentration side, the IV curve shifted upwards, indicating that the HIC membrane has excellent cation selectivity (A). Power tests were conducted using 0.5M and 10M KCl solutions. -2 A NaCl solution of M. Under a load of 5000 Ω, the power density of the HIC membrane exceeds 48 W / m³. 2 The HIC membrane, even after the fracture healed, still maintained a high strength of 44.12 W / m. 2 The power density (B) is low. HIC-N membranes lack self-healing ability and lose their permeation energy conversion function after rupture. HIC-S membranes have low cation selectivity and weak ion transport capacity, with a power density of only 1.6 W / m³. 2 (C, D).
[0045] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A high-strength, tough, self-healing, cationic-selective hydrogel membrane, characterized in that, The hydrogel membrane contains: i) A three-dimensional network formed by crosslinking polymerization of monomers containing carboxylic acid groups and monomers containing sulfonic acid groups in the presence of a crosslinking agent; ii) The polymer chain is selected from any one or a combination of two or more of poly(sodium 4-styrenesulfonate), poly(2-acrylamido-2-methyl-1-propanesulfonic acid), polyvinyl alcohol, or polyethylene glycol; and, iii) An ion transport medium comprising ethyl 1-ethyl-3-methylimidazolium sulfate and water; The three-dimensional network and the polymer chains interpenetrate and intertwine to form an interpenetrating network structure. The interpenetrating network structure is filled with an ion transport medium.
2. The hydrogel membrane according to claim 1, characterized in that, The carboxylic acid-containing monomer is selected from any one or a combination of two or more of acrylic acid, acrylates, alkyl acrylic acid, alkyl acrylates or alkyl acrylate esters; the sulfonic acid-containing monomer is selected from any one or a combination of two or more of alkylenylbenzene sulfonate, sulfoalkyl acrylate, alkylenamidoalkylpropanesulfonic acid or alkylenamidoalkylpropanesulfonic acid.
3. The hydrogel membrane according to claim 2, characterized in that, The carboxylic acid-containing monomer is selected from any one or a combination of two or more of acrylic acid, methacrylic acid, sodium methacrylate, magnesium methacrylate, calcium methacrylate, lithium methacrylate, potassium acrylate, ethyl methacrylate, methyl methacrylate, or hydroxyethyl methacrylate; the sulfonic acid-containing monomer is selected from any one or a combination of two or more of sodium 4-vinylbenzenesulfonate, lithium 4-vinylbenzenesulfonate, potassium 3-sulfopropyl acrylate, 2-acrylamido-2-methylpropanesulfonic acid, or sodium 2-acrylamido-2-methylpropanesulfonate.
4. The hydrogel membrane according to claim 1, characterized in that, The crosslinking agent is selected from acrylamide, acrylate, or phosphate crosslinking agents.
5. The hydrogel membrane according to claim 4, characterized in that, The crosslinking agent is selected from... N,N' - Any one or a combination of two or more of the following: methylene bisacrylamide, tripropylene glycol diacrylate, bis(2-(methacryloyloxy)ethyl) phosphate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, 1,3,5-triacryloyl hexahydro-1,3,5-triazine, or pentaerythritol tetraacrylate.
6. A composition for preparing the hydrogel membrane according to any one of claims 1 to 5, characterized in that, The composition comprises: The mixture contains 1-3 parts by weight of a carboxylic acid monomer, 3-5 parts by weight of a sulfonic acid monomer, 0.1-0.3 parts by weight of a polymer, 0.4-0.6 parts by weight of a crosslinking agent, 3-5 parts by weight of 1-ethyl-3-methylimidazolium sulfate, 3-5 parts by weight of deionized water, and an appropriate amount of initiator.
7. The composition according to claim 6, characterized in that, The initiator is selected from 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone or 2,2-azobisisobutylamidine dihydrochloride; And / or, the amount of the initiator is 0.04 to 0.06% of the total molar amount of the carboxylic acid monomer, the sulfonic acid monomer and the crosslinking agent.
8. A method for preparing the hydrogel membrane according to any one of claims 1 to 5, characterized in that, Prepared using the composition according to claim 6 or 7, wherein the preparation method comprises: Under light-protected conditions, a solution containing carboxylic acid monomers, sulfonic acid monomers, a polymer, a crosslinking agent, ethyl 1-ethyl-3-methylimidazolium sulfate, deionized water, and an initiator was prepared, and defoamed to obtain a precursor solution; and, Under oxygen-free conditions, the precursor solution is irradiated with ultraviolet light for a certain period of time to induce photo-curing, thereby obtaining the hydrogel film.
9. The preparation method according to claim 8, characterized in that, The power of the ultraviolet light irradiation is 100~200W, the wavelength of the ultraviolet light is 300~400nm, and the irradiation time is 20~40 min.
10. The application of the hydrogel membrane according to any one of claims 1 to 5 in reverse electrodialysis salinity gradient power generation.